2022
DOI: 10.1002/eco.2405
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomic structure but not the functioning of riparian herbaceous communities varies with hydrological conditions on a large, highly regulated river: Evidence from a 2‐year replicated study

Abstract: Riparian vegetation encompasses dynamic communities structured by strong environmental gradients. Due to anthropogenic changes, a greater uniformity of environmental conditions is observed along local gradients. To maintain diverse and functional communities in regulated rivers, there is an urgent need to finely characterize the factors controlling the spatial and temporal dynamics of riparian vegetation. In the summer of 2017 and 2019, we repeatedly sampled eight gravel bars along the regulated Rhône River. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Most of the pioneer species that characterise guild 3, i.e., meso‐eutro‐annual taproot species, but did not vary significantly between reaches. This indicates that even in highly anthropised rivers, and probably due to mechanical clearing of vegetation for flood risk management (Janssen, Chevalier, et al, 2022), pioneer plant communities can still find riparian habitats in which to establish, as evidenced on low‐lying bars made up of coarse‐grained sediments and more frequently flooded in the bypassed reaches of the Rhône River (Janssen, Piégay, & Evette, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the pioneer species that characterise guild 3, i.e., meso‐eutro‐annual taproot species, but did not vary significantly between reaches. This indicates that even in highly anthropised rivers, and probably due to mechanical clearing of vegetation for flood risk management (Janssen, Chevalier, et al, 2022), pioneer plant communities can still find riparian habitats in which to establish, as evidenced on low‐lying bars made up of coarse‐grained sediments and more frequently flooded in the bypassed reaches of the Rhône River (Janssen, Piégay, & Evette, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, our results showed that the abundance of perennial and clonal species in the communities increased in response to flow regulation and stabilisation, thereby promoting the biomass production process on the gravel bars. This leads to densification, stabilisation, and homogenisation of the vegetation cover with expected effects on the soil erosion control service, i.e., by protecting the bank and increasing the trapping of fine sediments, but also on the biodiversity support service, i.e., by decreasing the diversity of plant species, as shown by complementary studies on the Rhône River (Janssen et al, 2020; Janssen, Piégay, & Evette, 2022). This shift from response traits to effect traits, together with an understanding of the related processes, is, however, made possible by the individual analysis of variations in mean trait values.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more variables could be included in the modelling. The inclusion of vegetation types/species in the model (Hortobágyi et al, 2018; Janssen et al, 2022) may help in deciphering the spatial and temporal dynamics of vegetation regeneration. Additionally, quantification of anthropogenic factors is challenging as the point bars become enlarged through disposal of dredge sediment on bars and channel margins, but there is incomplete information on the disposal sites (Mossa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Riparian zones are critical ecosystems for biodiversity conservation on Earth and offer many ecosystem services to humanity (Rood et al, 2020;Janssen et al, 2022). The riparian plants stabilize the banks and surrounding land surfaces, filter sediment, modulate water nutrient content, and provide habitat for organisms (Gonzalez et al, 2017;Hoppenreijs et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, most current studies on biodiversity only look at TD, which largely ignores species differences in morphology, physiology, traits, and evolution (Yakimov et al, 2020). Despite the acknowledged importance of the FD and PD for maintaining ecosystem functions and providing ecosystem benefits (Grigoropoulou et al, 2022;Janssen et al, 2022), and recent investigations exploring the filtering of FD by flooding in subtropical reservoirs (Su et al, 2020), there has been insufficient exploration of the impact of flooding on PD in these areas (Dainese et al, 2015). Moreover, studies have shown that dimensions of biodiversity are unequally represented within protected areas and have additionally emphasized the need to apply an integrated perspective to protecting biodiversity (Cadotte and Tucker, 2018;Quan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%